Dietary inclusion of whole pomegranate by-product to improve oxidative stability of lamb meat - Natalello A.; Valenti B.; Pauselli M.; Mattioli S.; Bella M.; Luciano G.; Priolo A. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
This study evaluated the effect of dietary whole pomegranate by-product (WPB) on the oxidative stability of lamb meat. Seventeen Comisana lambs were divided into two groups and fed for 36 days: a barley-corn based concentrate diet (CON) or the same concentrate as the CON diet containing 20% of WPB to partially replace barley and corn (WPB). The dietary treatment did not affect the growth performance of lambs. Colour descriptors and metmyoglobin percentages were measured on longissimus dorsi (LD) muscle over 7 days of refrigerated storage. Lipid oxidation (TBARS values) was measured over time of refrigerated storage in raw and cooked muscle slices (7 days and 4 days, respectively). The dietary WPB increased the concentration of α-Tocopherol in LD (P < 0.001). Colour stability descriptors (a*, b* and H*) were affected by storage time, but not by dietary treatment. Metmyoglobin accumulated over time (P < 0.001), but WPB diet tended to decrease the overall metmyoglobin percentages (P = 0.051). TBARS values increased with time of storage (P < 0.001). WPB group showed lower TBARS values in cooked meat (P < 0.05). A significant interaction between dietary treatment and storage time was found for the TBARS value in raw meat (P = 0.013), with lower values found for WPB at 7 days of storage. The results highlight the positive effect of feeding lambs with WPB on meat shelf-life and demonstrate, for the first time, the contribution of α-Tocopherol (vitamin E) to this effect.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)